A 3D wireless charging cube with externally enhanced magnetic field for extended range of wireless power transfer. Issue 1 (3rd April 2019) - Zhu, Qi; Han, Hua; Su, Mei; Hu, Aiguo Patrick
Abstract : More mobile devices such as mobile phones and robots are wirelessly charged for convenience, simplicity, and safety, and it would be desirable to achieve three-dimensional (3D) wireless charging with high spatial freedom and long range. This paper proposes a 3D wireless charging cube with three orthogonal coils and supporting magnetic cores to enhance the magnetic flux outside the cube. The proposed system is simulated by Ansoft Maxwell and implemented by a downsized prototype. Both simulation and experimental results show that the magnetic cores can strengthen the magnitude of B-field outside the cube. The final prototype demonstrates that the power transfer distance outside the cube for getting the same induced electromotive force in the receiver coil is extended approximately by 50 mm using magnetic cores with a permeability of 2800. It is found that the magnitude of B-field outside the cube can be increased by increasing the width and the permeability of the magnetic cores. The measured results show that when the permeability of the magnetic cores is fixed, the induced electromotive force in the receiver coil at a point 300 mm away from the center of the cube is increased by about 2V when the width of the magnetic cores is increased from 50 to 100 mm. The increase in the induced electromotive force at an extended point implies a greater potential of wireless power transfer capability to the power pickup.